2007
DOI: 10.1021/ac061670b
|View full text |Cite
|
Sign up to set email alerts
|

Improving de Novo Sequencing of Peptides Using a Charged Tag and C-Terminal Digestion

Abstract: An improved method for peptide de novo sequencing by MALDI mass spectrometry is presented. The method couples a charge derivatization reaction with C-terminal digestion to modify tryptic peptides. The charge derivatization attaches a fixed charge group onto the N-termini of peptides, and the enzymatic digestion after the derivatization step removes C-terminal basic amino acid residues such as arginine and lysine. The fragmentation of the modified peptide(s) under low-energy CID conditions (MALDI Q-TOF mass spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 25 publications
0
43
0
Order By: Relevance
“…This charge derivatization produces better fragmentation and simpler spectra during collision activated dissociation experiments since an exclusive and often complete series of°N-terminal°fragment°ions°is°obtained° [34].°This derivatization procedure has also been applied successfully°to°tryptic°digests° [35].°In°the°case°of°MALDI experiments, where no additional proton is available that precludes the "mobile proton" model, this can be explained°by°charge-remote°fragmentation° [36,°37]. Very recently, coupling of TMPP derivatization with C-terminal digestion was shown to improve peptide de novo°sequencing°by°MALDI°MS° [38].…”
Section: Ecd Analysis Of Charge Derivatized (Tmpp) Peptidesmentioning
confidence: 99%
“…This charge derivatization produces better fragmentation and simpler spectra during collision activated dissociation experiments since an exclusive and often complete series of°N-terminal°fragment°ions°is°obtained° [34].°This derivatization procedure has also been applied successfully°to°tryptic°digests° [35].°In°the°case°of°MALDI experiments, where no additional proton is available that precludes the "mobile proton" model, this can be explained°by°charge-remote°fragmentation° [36,°37]. Very recently, coupling of TMPP derivatization with C-terminal digestion was shown to improve peptide de novo°sequencing°by°MALDI°MS° [38].…”
Section: Ecd Analysis Of Charge Derivatized (Tmpp) Peptidesmentioning
confidence: 99%
“…For example, the reagent tris(trimethoxyphenyl) phosphonium acetic acid N-hydroxysuccinimidyl ester (TMPP-AcOSu) can introduce a positive phosphonium ion on the Ntermini of peptides [16,27,28]. It does not decompose to produce a mobile proton like TMAB.…”
mentioning
confidence: 99%
“…Several studies demonstrated that the phosphonium ion is absolutely fixed at the Nterminus, and N-terminal a n ions are produced [16][17][18][19]29]. Recent studies also indicate that the fragmentation efficiency of arginine-containing charge-tagged peptides is low [20,28,30]. In fact, barely any sequence information can be obtained.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Keough and colleagues found that derivatization helped them to get long un-interrupted ion ladders [19]. Derivatization methods that simplify MS/MS spectra and fix the precursor charge to one of the fragments have been described [20,21]. Although derivatization may aid in de novo sequencing, such methods may not be widely adapted since they incur additional cost and labor.…”
Section: Introductionmentioning
confidence: 99%